Animal models of Huntington's disease for translation to the clinic: Best practices. Issue 11 (15th September 2014) - Menalled, Liliana; Brunner, Daniela; Reilmann, Ralf; Leavitt, Blair R.; Ross, Christopher A.
Abstract Mouse models of Huntington's disease (HD) recapitulate many aspects of the human disease. These genetically modified mice are powerful tools that are used not only to examine the pathogenesis of the disease, but also to assess the efficacy of potential new treatments. Disappointingly, in the past few years we have seen the success of potential therapies in animal studies, subsequently followed by failure in clinical trials. We discuss here a number of factors that influence the translatability of findings from the preclinical to the clinical realm. In particular, we discuss issues related to sample size, reporting of information regarding experimental protocols and mouse models, assignment to experimental groups, incorporation of cognitive measures for early phases of the disease, environmental enrichment, surrogate measures for survival, and the use of more than one HD mouse model. Although it is reasonable to question the appropriateness of the animal models used, we argue that it is more parsimonious to assume that improvements in experimental design and publication of negative results will lead to improved translatability to the clinic and insights about HD pathophysiology. © 2014 International Parkinson and Movement Disorder Society